Effect of Sodium Lauryl Sulfate-Fumaric Acid Coupled Addition on the In Vitro Rumen Fermentation with Special Regard to Methanogenesis. (29th October 2009) - Abdl-Rahman, M. A.; Sawiress, F. A. R.; Abd El-Aty, A. M.
Abstract : The aim of the current study was to evaluate the effect of sodium lauryl sulfate-fumaric acid coupled addition on in vitro methangenesis and rumen fermentation. Evaluation was carried out using in vitro gas production technique. Ruminal contents were collected from five steers immediately after slaughtering and used for preparation of inoculums of mixed rumen microorganisms. Rumen fluid was then mixed with the basal diet of steers and used to generate four treatments, negative control (no additives), sodium lauryl sulfate (SLS) treated, fumaric acid treated, and SLS-fumaric acid coupled addition treated. The results revealed that, relative to control, efficiency in reduction of methanogenesis was as follows: coupled addition > SLS-addition > fumaric acid addition. Both SLS-addition and SLS-fumaric acid coupled addition demonstrated a decremental effect on ammonia nitrogen (NH 3 –N ), total short chain volatile fatty acids (SCVFAs) concentrations and the amount of substrate degraded, and an increment effect on microbial mass and microbial yield (Y ATP ). Nevertheless, fumaric acid did not alter any of the previously mentioned parameters but induced a decremental effect onNH 3 –N . Furthermore, both fumaric acid and SLS-fumaric acid coupled addition increased propionate at the expense of acetate and butyrate, while, defaunation increased acetate at the expense of propionate and butyrate. The pH value was decreased by all treatments relative to control, while, cellulase activity did not differ by different treatments. The current study can be promising strategies for suppressing ruminal methane emissions and improving ruminants feed efficiency.